ANALISIS TINGKAT KECEMASAN DAN STRES ATLET FUTSAL SMP NEGERI 5 KOTA JAMBI - Prayogi, Julius Yogi; Nugraha, Ugi; Decheline, Grafitte (STKIP Melawi, 2025)
Abstract: This study aims to analyze the level of anxiety and stress in futsal athletes of SMP Negeri 5 Jambi City as an effort to understand the psychological factors that affect the performance of adolescent athletes. The background of this activity is based on the importance of mental health in the world of sports, especially among students who are vulnerable to pressure from both the school environment and the demands of achievement. The method used in this study was a quantitative approach by distributing standardized anxiety and stress questionnaires to all members of the school futsal team. The data collected were then analyzed descriptively and inferentially to determine the level and relationship between anxiety and stress on their sports activities. The results showed that the majority of athletes were at moderate levels of anxiety and stress, with some individuals showing high levels ahead of important matches. Keywords: Anxiety, Stress, Futsal Abstrak: Penelitian ini bertujuan untuk menganalisis tingkat kecemasan dan stres pada atlet futsal SMP Negeri 5 Kota Jambi sebagai upaya memahami faktor psikologis yang memengaruhi performa atlet remaja. Latar belakang kegiatan ini didasari oleh pentingnya kesehatan mental dalam dunia olahraga, khususnya di kalangan pelajar yang rentan mengalami tekanan baik dari lingkungan sekolah maupun tuntutan prestasi. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan penyebaran kuesioner standar kecemasan dan stres kepada seluruh anggota tim futsal sekolah. Data yang dikumpulkan kemudian dianalisis secara deskriptif dan inferensial untuk mengetahui tingkat serta hubungan antara kecemasan dan stres terhadap aktivitas keolahragaan mereka. Hasil penelitian menunjukkan bahwa mayoritas atlet berada pada tingkat kecemasan dan stres sedang, dengan beberapa individu menunjukkan tingkat yang tinggi menjelang pertandingan penting. Kata Kunci: Kecemasan, Stres, Futsal